2019 International Symposium on Multi-Robot and Multi-Agent Systems (MRS) 2019
DOI: 10.1109/mrs.2019.8901058
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Multi-Floor Exploration by a Swarm of Miniature Robots Teaming with Wall-Climbing Units

Abstract: In this paper, we consider the problem of collectively exploring unknown and dynamic environments with a decentralized heterogeneous multi-robot system consisting of multiple units of two variants of a miniature robot. The first variant-a wheeled ground unit-is at the core of a swarm of floor-mapping robots exhibiting scalability, robustness and flexibility. These properties are systematically tested and quantitatively evaluated in unstructured and dynamic environments, in the absence of any supporting infrast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…To validate the obtained simulation results, we performed series of experiments using 6 in-house developed differential-drive land robots with a maximum speed of 10 cm/s. Although this swarm robotic system was originally developed for the mapping of unknown environments (see Kit et al (2019) for technical details), it has also been used in the tracking of non-evasive targets (Kwa et al, 2020a).…”
Section: Swarm Robotic Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the obtained simulation results, we performed series of experiments using 6 in-house developed differential-drive land robots with a maximum speed of 10 cm/s. Although this swarm robotic system was originally developed for the mapping of unknown environments (see Kit et al (2019) for technical details), it has also been used in the tracking of non-evasive targets (Kwa et al, 2020a).…”
Section: Swarm Robotic Experimentsmentioning
confidence: 99%
“…This includes system flexibility-the ability to operate in dynamic environments, robustness-the ability to cope with individual agent failures, and scalability-the ability to carry out tasks in systems comprised of different number of agents. As such, swarming MRS have been demonstrated to be able to carry out several tasks such as dynamic area monitoring (Zoss et al, 2018), area mapping (Kit et al, 2019), and target monitoring (Coquet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the robot's vision, it has been found that common ranging modules are usually bulky (Sundram et al, 2018). Hence, we develop a custombuilt light detection and ranging (LiDAR) module to reconstruct the point cloud of the environment for the miniature robots, thus enabling the real-time construction of an occupancy grid map (Kit et al, 2019). As the ranging module requires clear line-ofsight, it is impractical to develop it on Virgo.…”
Section: Virgo: Miniaturization Effortmentioning
confidence: 99%
“…Add-on sensor Reconfiguration wheel To achieve adaptability and heterogeneity for the miniature robots, the architecture of the Orion platform is classified into two parts: (1) the chassis, which is the main uniform element that would house the electronics and technologies developed by other platforms; (2) the wheels, which are reconfigurable depending on the requirements. There are two species of Orion developed for the specific application of indoor urban sensing and mapping: ground-mapping Orion (O-map) and wall-climbing Orion (O-climb) (Kit et al, 2019).…”
Section: Common Chassismentioning
confidence: 99%